Seminoma arising in splenogonadal fusion: a case report and literature review - Donglai Shen; Yuzhu Li; Yu Zhang; Xiao Chang; Xupeng Zhao; Jiabin Li; Xu Zhang; Gang Guo (BMC, 2023)
Abstract Background Splenogonadal fusion (SGF) is a rare congenital malformation in which the spleen is abnormally connected to the gonads or to the mesonephric derivatives. There is no obvious causality between SGF and testicular neoplasm. However, cryptorchidism, which is a well-known risk factor of testicular germ cell tumors, are the most frequent malformations associated with SGF. To our knowledge, there are only four reported cases of SGF associated with testicular neoplasm so far. Herein, we reported a patient of this condition, and briefly reviewed the related literature. Case presentation A 48-year-old man was diagnosed with bilateral cryptorchidism 30 years prior, and only underwent a right orchiopexy for the left testicle could not be explored during the operation. At that time, doctors failed to realize the possibility of SGF due to the lack of sufficient knowledge of this condition. This time, the patient was treated for a left abdomen mass that was diagnosed as stage III metastatic seminoma. Then, a right orchiectomy, robot-assisted laparoscopic left retroperitoneal tumor resection, and left retroperitoneal lymph node dissection was performed after four cycles of BEP (bleomycin + etoposide + cisplatin) systemic chemotherapy in our center. The final diagnosis of SGF was made by postoperative pathology. The patient was re-examined in our center at 3 months and 6 months after the operation, and no obvious abnormalities were found. Conclusions Surgeons should always bear in mind the possibility of association between bilateral cryptorchidism and splenogonadal fusion to avoid malignant transformation caused by delayed treatment.